The association of maternal smoking and other sociobehavioral factors with dental caries in toddlers: A cross-sectional study - Sobiech, Piotr; Olczak-Kowalczyk, Dorota; Spodzieja, Karolina; Gozdowski, Dariusz (Frontiers in Pediatrics, 2023)
BACKGROUND: Dental caries in toddlers is a severe form of early childhood caries (S-ECC), which can strongly affect general health and quality of life. Studies on factors that can contribute to the development of caries immediately after tooth eruption are sparse. The aim of this study was to assess the role of sociobehavioural factors and pre- and postnatal exposure to tobacco smoke in the aetiology of dental caries in children up to 3 years old. METHODS: A cross-sectional study was conducted between 2011 and 2017 to assess oral health and teething in urban children 0-4 years of age. The number of teeth and surfaces with spot lesions (d1,2), as well as decayed (d), missing (m), and filled (f) teeth classified according to ICDAS II was evaluated in a dental office setting. d1,2dmft and d1,2dmfs were calculated. Severe early childhood caries was diagnosed for d1,2dmfs > 0. Parents completed a self-administered questionnaire on socioeconomic factors, maternal health, course of pregnancy, child’s perinatal parameters, hygiene and dietary practices, as well as maternal smoking during and after pregnancy. Data on children aged 12-36 months were collected and analysed statistically using the t-test, Spearman rank correlations and prevalence ratios (PR). Significance level was set at 0.05. RESULTS: Dental caries was found in 46% of 496 children aged 12-36 months. Mean d1,2dmft and d1,2dmfs were 2.62±3.88 and 4.46±8.42, respectively. Tobacco smoking during and after pregnancy was reported by 8.9% and 24.8% of women, respectively. Spearman's rank correlation analysis confirmed a relationship between S-ECC and parental education, maternal smoking, bottle feeding, avoiding springy foods, number of meals, and the age of tooth brushing initiation. Pre- and postnatal exposure to tobacco smoke (APR=1.32, 95% CI 0.99,1.76) and only postnatal (APR=1.14 95% CI (0.89,1.44) increased the risk of S-ECC. Maternal smoking was correlated with the level of education and dietary practices. CONCLUSIONS: Our study confirmed the relationship between dental caries in toddlers and pre- and postnatal smoking. Both maternal smoking and the child's tooth decay are associated with poor parental education and other improper oral health behaviours.